How to promote resilience in the supply chain in the context of COVID-19? An exploratory study using the Delphi method - Devisson Mesquita dos Santos; Fernanda Leandra Leal Lopes; André Cristiano Silva Melo; Denilson Ricardo de Lucena Nunes; Izabela Simon Rampasso; Vitor William Batista Martins (Modern Supply Chain Research and Applications, 2024)
Purpose This paper is dedicated to elaborating, proposing and validating an action plan to enhance the mitigation of risks generated by the COVID-19 pandemic in the electric sector supply chain, aiming to promote a more resilient supply chain. Design/methodology/approach For this, a systematic review of the literature was carried out to prepare an action plan that was validated by a group of experts, through the Delphi methodology. Findings As a result, an action plan was obtained, with 18 actions subdivided into 13 resilience elements and related to 20 main risks arising from the pandemic. The actions oriented to the development of relationships among supply chain members, promotion of a culture oriented to learning and problem solving, contingency plan, safety stock and risk management were pointed as those capable of generating resilience in the chain analyzed in the moment of crisis. Originality/value The results achieved can contribute to the expansion of debates in the area of resilient supply chain management, as well as contribute to supply chain managers in their elaboration and definition of actions that aim to make the supply chain more resilient. It is noteworthy that no similar study was found in the literature considering the specificities of supply chain management in the Brazilian Amazon region.
Keywords: 650; COVID-19; Electric sector; Resilience; Risk management; Supply chain